2006
DOI: 10.1348/014466605x82341
|View full text |Cite
|
Sign up to set email alerts
|

Temporality and collectivity: Diversity, history and the rhetorical construction of national entitativity

Abstract: Vernacular representations of nationhood collected in England differed from canonical accounts of social categorization in three respects. First, nations were not typically constructed as simple person categories, but rather as hybrid collectivities of human beings, objects and geographical locations. Second, national representation was not confined to the present tense, but was typically conveyed through temporal distinctions and narratives. Third, speakers displayed a reflexive concern over the rationality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 62 publications
4
109
0
3
Order By: Relevance
“…This idea of negative progress from past to present has also been noted in other contexts (i.e. Billig, 1992;Condor, 2006;Van Alphen & Carretero, 2015). With regards to migration, Mols and Jetten (2014) show how a representation of the past in glorious terms in opposition to a present decline and a bleak future can be used to legitimise anti-immigrant positions.…”
Section: Idealisation Of the Pastsupporting
confidence: 68%
“…This idea of negative progress from past to present has also been noted in other contexts (i.e. Billig, 1992;Condor, 2006;Van Alphen & Carretero, 2015). With regards to migration, Mols and Jetten (2014) show how a representation of the past in glorious terms in opposition to a present decline and a bleak future can be used to legitimise anti-immigrant positions.…”
Section: Idealisation Of the Pastsupporting
confidence: 68%
“…However, given the suggestions made by Brewer (1999), Condor (2006), Fu et al (1999), Gallagher (1989Gallagher ( , 1993 and Tajfel (1966), it is suggested that future research should build on the findings of the current study and take a more qualitative approach to researching the identities of this diasporic group, ideally determining the meanings behind the identity labels for members of the Irish and Northern Irish diaspora. This would allow for a more detailed and intricate look at the meaning of identity in diaspora and would also allow for a more inclusive sample in terms of the ages of participants.…”
Section: Discussionmentioning
confidence: 91%
“…Further research by Gallagher (1989;1993) suggests that although a label may give name to an identity, it does nothing to indicate the significance of that identity or the meaning that is assigned to that label. Further, as Condor (2006) suggests, individuals' accounts of their identity are "necessarily chronically tensed" and if future research is to engage in a more temporal unravelling of these identity issues then a narrative approach, which heeds Tajfel's (1966, p.79) concern for "those abstract and symbolic aspects of human imagination" may be better placed to attend to the "complex and often dilemmatic aspects of respondents' accounts" (Condor, 2006, p.667).…”
Section: Discussionmentioning
confidence: 94%
“…Thus there is no concrete 'them' contrasted with 'us'; rather, the sole unifying feature of the implicit outgroup is that they are not us. The fact that such arguments can be made at all reflects the extent to which speakers can take for granted a shared ingroup frame of reference that -while not relying on any common features by virtue of shared categorical membership (Condor, 2006) -nevertheless can be assumed to share the basic and powerful assumption that, whoever we are, we take priority in our country.…”
Section: Individualizing Immigration 26mentioning
confidence: 99%